Paraprobiotic derived from Bacillus velezensis GV1 improves immune response and gut microbiota composition in cyclophosphamide-treated immunosuppressed mice - Lee, Hyo-Jun; Tran, My Thi Hoa; Le, Minh Ha; Justine, Elsa Easter; Kim, Yeon-Ju (Frontiers in Immunology, 2024)
Paraprobiotics that benefit human health have the capacity to modulate innate and adaptive immune systems. In this study, we prepared the paraprobiotic from Bacillus velezensis GV1 using the heat-killing method and investigated its effects on immunity and gut microbiota in vitro and in vivo. The morphology of inactivated strain GV1 was observed using scanning electron microscopy. Treatment with GV1 promoted nitric oxide production and augmented cytokine (IL-6, IL-1β, and TNF-α) expression and secretion in RAW 264.7 macrophages.Moreover, the strain GV1 could alleviate cyclophosphamide monohydrate (CTX)-induced immunosuppression by reversing spleen damage and restoring the immune organ index, as well as by increasing the expression of immune-related cytokines (TNF-α, IL-1β, in the spleen and thymus, respectively. Furthermore, GV1 treatment dramatically healed the CTX-damaged colon and regulated gut microbiota by increasing the relative abundance of beneficial bacterial families (Lactobacillaceae, Akkermansiaceae, and Coriobacteriaceae) and decreasing that of harmful bacterial families (Desulfovibrionaceae, Erysipelotrichaceae, and Staphylococcaceae). Thus, the heat-killed GV1 can be considered a potential immunoregulatory agent for use as a functional food or immune-enhancing medicine.